PENGEMBANGAN LKPD BERBASIS METODE PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN PSIKOMOTORIK SISWA KELAS V SEKOLAH DASAR - Juni Firman Karisma; Bistari Bistari; Suparjan Suparjan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study aims to develop a paper product for students based on a question-based learning curve to improve students' psychomotor learning skills in Theme 3 sub-theme 2, 5th grade primary. The research method used is research and development (RnD) by adopting the ADDIE model. The data sources for this study were media professionals, hardware experts, a teacher, and fifth graders. The test materials used were interview guides, pre-test questionnaires, media expert support questions, material support questions, student feedback questions and documents. Student workbooks have a professional rating based on a professional grade point average of 4.9 with good grades and media professionals with a grade point average of 4.0 with good grades. The scope of the student workbook based on the response to student assessment is 4.5 with good grades. Psychomotor students after taking LKPD, small-scale learning-based learning rate was 84.17%, and large-scale application rate was 84.02%.Keywords: Inquiry, Psychomotor, Student Worksheet